OBSTACLES ENCOUNTERED WHILE INTEGRATING LITERATURE IN TEACHING ENGLISH - Yulnetri Yulnetri (Ta'dib, 2018)
This article depicts problems faced by High School teachers while using literature in teaching English. The data related to their broad views of using literature in the classroom were obtained from semi structured questionnaires as the preliminary data distributed to English teachers in Tanah Datar regency. As the result, by using purposive sampling technique ten of the teachers were selected to be the informants of the research. Then, in-depth interviews were conducted to the informants in order to find the obstacles encountered while integrating literature in their teaching of English. As the result, most of the informants found that using literature is interesting, however it is relatively disadvantageous because of several burdens, such as 1) Its difficult language, in terms of its complexity, its structure, vocabulary, poetic and unfamiliar diction, 2) inappropriacy with the students’ level, 3) not suitable with the topics, 4) time management, 5) students’ lack of pronunciation, 6) unavailable supporting tools, 7) limited resources, 8) students’ unconfidence, and 9) unattractive poem materials.